Political theory and power - Joseph, Sarah (Delhi, 2007)
The concept of power is of central importance for political theory. But it is a particularly elusive concept because it refers to a complex set of relationships which are manifested at different levels of social life. This book analyzes the concept of power in some important political theories of the contemporary period. It draws attention to certain significant changes in the way in which power has been defined and it also examines some of the critical responses which those changes have evoked. The objective is not to try and evolve a universally acceptable and comprehensive definition of power, and of related terms like authority, and influence. The argument of the book is that, that would be an impossible project since social and political theories themselves constitute an intervention into political discourse of a society and they may, implicitly or explicitly, embody a political perspective. The basic assumptions about society embodied in a theory may be expressed through certain ordering concepts and a particular mode of theorizing. Since political stances and theoretical trends influence the way in which power is conceptualized, we can only understand the significance and possible limitations of different concepts of power by analyzing them with reference to the theories and political perspective which generate them. It is hoped that such analysis would provoke critical thinking about the concept of power and about the kind of policy initiatives it may have helped to support.
Keywords: Political science